The Effect of Adding Catfish (Clarias gariepinus) Bone Flour to Cassava Crackers (Manihot esculenta) on Calcium Content and Sensory Attribute - Nuraini, Azizah; Zulfahmi, A Nova; Setiawan, Feri; Afiyah, Novia Nurul (Jurnal Ilmu Pangan dan Hasil Pertanian, 2025)
This study aimed to utilize catfish (Clarias gariepinus) bone flour as a calcium fortification ingredient in cassava crackers (opak) and to determine the optimal substitution level based on calcium content and sensory quality. Catfish bone waste generated from shredded fish processing industries has potential as a source of calcium, phosphorus, and collagen, which can enhance the nutritional value of starch-based food products. The study employed four levels of substitution: T1 (0%), T2 (5%), T3 (10%), and T4 (15%) catfish bone flour. The cracker production process consisted of ingredient mixing, steaming for 15 minutes, drying at 50°C for 24 hours, and deep-frying. Calcium content was analyzed using Atomic Absorption Spectrophotometry (AAS), while sensory evaluation was carried out using a 1–5 hedonic scale with 30 panelists. The results showed that increasing the concentration of catfish bone flour led to higher calcium content. The lowest calcium level was observed in T1 at 431.31±21.3 mg/100 g, whereas the highest was recorded in T4 at 983.51±13.7 mg/100 g. Sensory evaluation indicated that T3 was the most preferred formulation, with color, aroma, taste, and texture scores of 4.4±0.5, 4.3±0.5, 4.5±0.5, and 4.4±0.5, respectively. The addition of 10% catfish bone flour provided the best balance between enhanced nutritional value and panelist acceptance. Therefore, a 10% substitution level is recommended as the optimal formulation for producing calcium-rich cassava crackers that remain acceptable to consumers while supporting the sustainable utilization of fish by-products.